Archaeology of domestic landscapes of the enslaved in the Caribbean - Delle, James A.; Clay, Elizabeth C. (Ripley P. Bullen series., 2019)
This volume examines, through the analysis of archaeological evidence collected from a wide variety of sites across the region, the diversity of living environments that the enslaved inhabited in the colonial Caribbean. This book brings together case studies of Caribbean slave settlements as a means of exposing the diversity of people and practices in these various settings across the British, French, Dutch, and Danish colonies in both the Greater and Lesser Antilles as well as the Bahamian archipelago.